An acoustical study of English Plosives in word initial position produced by Malays - Shahidi A.H,; Rahim Aman, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper presents key findings from a study on the realisation of the initial plosives voicing contrast in the speech performance of learners of English whose first language is Malay. This paper also presents the results of an acoustic study of the Malay voicing contrasts with a focus on acoustic measures. Waveform and spectrogram samples were used for segmentation of utterances and for obtaining values for each measurement. Measurements were taken of VOT of initial phase of selected segments occurring singly. VOT measurements were made (to the nearest msec) from the plosive release burst to the first periodic cycle of the vowel. The release burst refers to the point at which there was a sudden spread in spectral energy indicating articulatory release. For the prevoiced tokens, VOT was measured from the onset of periodicity (which shows a visible periodic signal with low frequency energy) and assigned a negative value. Results are then presented on the realisation of the voicing contrast in English spoken by Malay speakers. The results are discussed in light of the acquisition of L2 (English) sound patterning, focusing in particular on the situation presented by acquiring L2 within an L1 (Malay) context. This study (via spectrographic analysis) demonstrates that where there is phonemic similarity (but phonetic dissimilarity) across Malay and English, L1 phonetic properties are found to be strong for Malay learners of English in the L1 environment.